2013
DOI: 10.1152/ajpendo.00512.2012
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet-induced hyperinsulinemia and tissue-specific insulin resistance inCry-deficient mice

Abstract: van der Horst GT, Oster H. High-fat diet-induced hyperinsulinemia and tissue-specific insulin resistance in Cry-deficient mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
101
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 58 publications
3
101
2
1
Order By: Relevance
“…CRY1, a key regulator of the inhibitory arm of circadian rhythmicity, has been implicated as a key modulator of the intrinsic liver clock: the Cry1 gene is rhythmically expressed, with higher protein levels seen during the transition from night to day, where CRY1 reduces hepatic gluconeogenesis [8]. Mice deficient in CRY1 that are kept on a high-fat diet gain less weight than their wild-type littermates despite comparable levels of energy intake, whereas mice deficient in both CRY1 and CRY2 are susceptible to obesity despite lower energy intake, and show enhanced insulin secretion [9,10]. When fed normal chow, mice deficient in CRY1 or CRY2 do not differ phenotypically from wild-type mice [10], whereas mice deficient in both CRY1 and CRY2 gain less fat mass and increase their basal metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRY1, a key regulator of the inhibitory arm of circadian rhythmicity, has been implicated as a key modulator of the intrinsic liver clock: the Cry1 gene is rhythmically expressed, with higher protein levels seen during the transition from night to day, where CRY1 reduces hepatic gluconeogenesis [8]. Mice deficient in CRY1 that are kept on a high-fat diet gain less weight than their wild-type littermates despite comparable levels of energy intake, whereas mice deficient in both CRY1 and CRY2 are susceptible to obesity despite lower energy intake, and show enhanced insulin secretion [9,10]. When fed normal chow, mice deficient in CRY1 or CRY2 do not differ phenotypically from wild-type mice [10], whereas mice deficient in both CRY1 and CRY2 gain less fat mass and increase their basal metabolic rate.…”
Section: Discussionmentioning
confidence: 99%
“…In human islets, the expression of CRY2 mRNA has been shown to be negatively correlated with levels of glycated haemoglobin, and the expression of CRY2 mRNA was lower in participants with type 2 diabetes [7]. Several recently published studies have further indicated the importance of CRY2 and its circadian co-regulator CRY1 on glucose metabolism and energy homeostasis in mice [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin secretion from pancreatic beta cells is clock-gated, and disruption of the positive arm of the clock -CLOCK or BMAL1 -results in hypoinsulinemia (Marcheva et al 2010, Sadacca et al 2011, while disruption of the clock's negative regulators -PERs and CRYs -is associated with hyperinsulinemia (Zhao et al 2012, Barclay et al 2013. Insulin sensitivity is reduced in shift workers, and accompanied by increased beta cell activity, suggesting a pre-diabetic state (Esquirol et al 2012).…”
Section: Ghrelin and Insulinmentioning
confidence: 99%
“…While Cry double-mutant mice show dampened feeding rhythms on normal chow diet (NCD) and HFD, they are generally lighter and leaner than wild-type controls. 7,40,68 Under HFD, however, they rapidly gain weight despite a lower food intake compared to wild types. 40 This effect is explained by an enhanced potential of Cry-mutant adipocytes for lipid uptake and insulin-stimulated lipogenesis, making them highly susceptible to HFD-induced obesity.…”
Section: -60mentioning
confidence: 99%
“…36,[38][39][40] This example highlights the complex interaction of cellular adipose clocks with external signals (e.g., food composition and gender effects) in adipocyte differentiation.…”
mentioning
confidence: 99%